2008
DOI: 10.1037/1076-898x.14.3.201
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating warning sound urgency with reaction times.

Abstract: It is well-established that subjective judgments of perceived urgency of alarm sounds can be affected by acoustic parameters. In this study, the authors investigated an objective measurement, the reaction time (RT), to test the effectiveness of temporal parameters of sounds in the context of warning sounds. Three experiments were performed using a RT paradigm, with two different concurrent visuomotor tracking tasks simulating driving conditions. Experiments 1 and 2 show that RT decreases as interonset interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 40 publications
(69 reference statements)
5
46
0
Order By: Relevance
“…Results are equivocal from the limited existing research. For example, Suied, Susini, and McAdams (2008) and Haas and Casali (1995) both found negative correlations between perceived urgency and response time. Suied et al also found that response time decreased as the time between auditory pulses decreased, though they caution that the underlying mechanisms involved may be unrelated.…”
Section: Introductionmentioning
confidence: 99%
“…Results are equivocal from the limited existing research. For example, Suied, Susini, and McAdams (2008) and Haas and Casali (1995) both found negative correlations between perceived urgency and response time. Suied et al also found that response time decreased as the time between auditory pulses decreased, though they caution that the underlying mechanisms involved may be unrelated.…”
Section: Introductionmentioning
confidence: 99%
“…Four sounds were tested in each category. For the classical warning sounds, we used the same template for the stimuli as in our companion paper (Suied et al, 2008). The template for the different stimuli was an isochronous sequence of short pulses.…”
Section: Methodsmentioning
confidence: 99%
“…Loudness equalization was performed on the eight stimuli to avoid any RT differences due to loudness differences (see Chocholle, 1940;Suied et al, 2008). A group of nine other listeners participated in this preliminary experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have already focused on the importance of distinctive parameters of sounds. Suied evaluated the influence of some acoustic parameters on reaction time [18]. Edworthy et al [19], suggested that improvement of existing auditory warning systems can be done by 'fitting' some acoustic parameters to specific needs.…”
Section: Discussionmentioning
confidence: 99%